2023
DOI: 10.1002/smll.202301939
|View full text |Cite
|
Sign up to set email alerts
|

Cracked Film Lithography with CuGaOx Buffers for Bifacial CdTe Photovoltaics

Abstract: sun front illumination efficiency). The backsheet is then replaced with glass at an added cost of only $0.01/W DC,peak for PERC modules. These simple process changes lead to projections of ≈10% more power output over the lifetime of the module, [3] although 5-33% bifacial power gains have been reported. [4] In parallel with the expansion of bifacial PV, the thin-film PV market has also transformed: CdTe accounted for just 2.5% of total and 70% of thin-film shipped capacity in 2017, but these percentages rose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Despite these increases in sheet resistance, the impact on the EMI SE was not significantly pronounced (Figure 7b). After the bending tests, the average SE for samples 1 through 5 changed The following works in the literature are shown: Cu mesh(Liu), 67 Ag mesh (Cui), 68 graphene/Ni mesh, 32 Ti/Ag meshes, 73 Ag mesh (Han), 69 Ag mesh (Rao and Gupta), 76 Ag mesh (Xian), 71 Ag mesh (Gupta), 79 Ag mesh (Rao and Hunger), 80 Au mesh (Guo), 81 Ag mesh (Kang), 74 Au mesh (Muzzillo), 70 and Ag mesh (Voronin). from 42.5 to 41.4, from 42.0 to 39.5, from 37.4 to 35.6, from 39.7 to 37.6, and from 38.3 to 38.1 dB, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these increases in sheet resistance, the impact on the EMI SE was not significantly pronounced (Figure 7b). After the bending tests, the average SE for samples 1 through 5 changed The following works in the literature are shown: Cu mesh(Liu), 67 Ag mesh (Cui), 68 graphene/Ni mesh, 32 Ti/Ag meshes, 73 Ag mesh (Han), 69 Ag mesh (Rao and Gupta), 76 Ag mesh (Xian), 71 Ag mesh (Gupta), 79 Ag mesh (Rao and Hunger), 80 Au mesh (Guo), 81 Ag mesh (Kang), 74 Au mesh (Muzzillo), 70 and Ag mesh (Voronin). from 42.5 to 41.4, from 42.0 to 39.5, from 37.4 to 35.6, from 39.7 to 37.6, and from 38.3 to 38.1 dB, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(a) Transmission at 550 nm versus sheet resistance and (b) σ DC /σ OP versus sheet resistance. The following works in the literature are shown: Cu mesh­(Liu), Ag mesh (Cui), graphene/Ni mesh, Ti/Ag meshes, Ag mesh (Han), Ag mesh (Rao and Gupta), Ag mesh (Xian), Ag mesh (Gupta), Ag mesh (Rao and Hunger), Au mesh (Guo), Ag mesh (Kang), Au mesh (Muzzillo), and Ag mesh (Voronin) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Recently, Muzzillo et al demonstrated a combined CuGaO x and templated Au nanogrid contact with 19.2% frontside efficiency and 2.5% backside efficiency. 10 This hierarchical approach is extended in this work to use a copper-free AlGaO x buffer layer, a conductive and semitransparent Ti 3 C 2 T x interlayer with a high work function, and a highly conductive patterned gold nanogrid grid to lower series resistance. Solution-processed AlGaO x hole transport layers have a tunable band gap based on the ratios of aluminum and gallium precursors.…”
mentioning
confidence: 99%